New Achievements for the Treatment of Triple-Negative Breast Cancer - Alessia Catalano; Domenico Iacopetta; Jessica Ceramella; Annaluisa Mariconda; Camillo Rosano; Domenica Scumaci; Carmela Saturnino; Pasquale Longo; Maria Stefania Sinicropi (Applied Sciences, 2022)
Triple-negative breast cancer (TNBC) constitutes a heterogeneous group of malignancies that are often aggressive and associated with a poor prognosis. The development of new TNBC treatment strategies has become an urgent clinical need. Diagnosis and subtyping of TNBC are essential to establish alternative treatments and targeted therapies for every TNBC patient. Chemotherapy, particularly with anthracycline and taxanes, remains the backbone for medical management for both early and metastatic TNBC. More recently, immune checkpoint inhibitors and targeted therapy have revolutionized cancer treatment. Included in the different strategies studied for TNBC treatment is drug repurposing. Despite the numerous medications available, numerous studies in medicinal chemistry are still aimed at the synthesis of new compounds in order to find new antiproliferative agents capable of treating TNBC. Additionally, some supplemental micronutrients, nutraceuticals and functional foods can potentially reduce the risk of developing cancer or can retard the rate of growth and metastases of established malignant diseases. Finally, nanotechnology in medicine, termed nanomedicines, introduces nanoparticles of variable chemistry and architecture for cancer treatment. This review highlights the most recent studies in search of new therapies for the treatment of TNBC, along with nutraceuticals and repositioning of drugs.